Self-selected and maximal walking speeds provide greater insight into fall status than walking speed reserve among community-dwelling older adults - Middleton, Addie (Am J Phys Med Rehabil, 2016)
OBJECTIVE: To determine the degree to which self-selected walking speed (SSWS), maximal walking speed (MWS), and walking speed reserve (WSR) are associated with fall status among community-dwelling older adults. DESIGN: WS and one-year falls history data were collected on 217 community-dwelling older adults (median age=82, range 65-93 years) at a local outpatient PT clinic and local retirement communities and senior centers. WSR was calculated as a difference (WSRdiff=MWS-SSWS) and ratio (WSRratio=MWS/SSWS). RESULTS: SSWS (p<0.001), MWS (p<0.001), and WSRdiff (p<0.01) were associated with fall status. The cutpoints identified were 0.76 m/s for SSWS (65.4% sensitivity, 70.9% specificity), 1.13 m/s for MWS (76.6% sensitivity, 60.0% specificity), and 0.24 m/s for WSRdiff (56.1% sensitivity, 70.9% specificity). SSWS and MWS better discriminated between fallers and non-fallers (SSWS: AUC=0.69, MWS: AUC=0.71), than WSRdiff (AUC=0.64). CONCLUSIONS: SSWS and MWS appear to be equally informative measures for assessing fall status in community-dwelling older adults. Older adults with SSWSs less than 0.76 m/s and those with MWSs less than 1.13 m/s may benefit from further fall risk assessment. Combining SSWS and MWS to calculate an individual's WSR does not provide additional insight into fall status in this population.